Controlling of β grain structure and α phase in wire-arc directed energy deposition Ti–6Al–4V by using plasma deep melting - Wenbo Du; Chuanchuan Jia; Chao Chen; Guorui Sun (Journal of Materials Research and Technology)
This work reported the β grain structure and α phase in wire-arc-directed energy deposition (DED-arc) Ti–6Al–4V by using a plasma deep melting treatment DED-arc Ti–6Al–4V component surface. After the introduction of plasma deep melting treatment, the DED arc Ti–6Al–4V component in the remelting region and no-remelting region had the same microstructure and consisted of coarse columnar β grains, basket-weave structures and acicular α′; however, the morphology and size of the microstructure obviously changed, such as the coarse columnar β grains broken by the remelting region, the refined basket-weave structures and acicular α′ obtained in the remelting region. The texture intensity of the α and β phases was also reduced under the action of the plasma deep melting treatment. The decrease in the average size of the prior-β grains strengthened the fine grains, and the α phase was refined to increase the dislocation density to strengthen the material. Therefore, compared with that of traditional samples, the tensile strengths of samples subjected to plasma deep melting in the building direction and deposition direction were increased by approximately 6.9 % and 8.3 %, respectively.